Effect of maize variety and storage form on the development of the maize weevil, Sitophilus zeamais Motschulsky - Vowotor, K.A.; Bosque Pérez, N.A.; Ayertey, J. (Elsevier, 1995)
The effects of maize variety and storage form on development of the maize weevil, Sitophilus zeamais Motschulsky, were studied under artificial infestation at 25 ± 2 °C and 70 ± 5% r.h. in the laboratory. Three improved West African maize varieties, Abeleehi, EV8725-SR, Pop63-SR and the local variety, Volta Local, stored shelled and as cobs without husks (=unshelled) were used. Dissections of infested grain were used to monitor insect development at regular intervals. Maize variety and storage form had a significant effect (P < 0.05) on the mean duration of most developmental stages. Across varieties, the mean total duration of larval stages (first to fourth) was 25.2 d on unshelled grain vs 22.8 d on shelled grain. By day 30, 76% of third instar larvae in shelled kernels had tunnelled to the germ and fed on the radicle and scutellum portions compared to 44% of the larvae in unshelled grain. The pre-emerged adult spent 5.3 d longer in unshelled than in shelled maize. The mean weights of the developing insect (across varieties) were not significantly influenced by storage form, except for the first and third instar larvae, which gave higher mean weights on shelled than unshelled grain. Both maize variety and storage form influenced the site of weevil emergence from the kernel.